Medical organizational model for prevention of cardiovascular complications in patients with atrial fi brillation based on clinical physiological assessment of risk factors - R. S. Goloshchapov-Aksenov; A. V. Fomina; O. V. Rukodaynyy; D. I. Kicha; A. G. Koledinsky; S. A. Bagin; E. A. Makaryan; P. S. Volkov (Russian neurological journal, 2026)
Introduction . Improving the prevention of cardiovascular complications (CVC) is an actual problem. Clinical physiological analytics (CPA) provides an evidence basis for selecting a personalized model prevention ov CVC. Purpose : тo develop a medical organizational model for prevention of cardiovascular complications (CVC) in patients with atrial fibrillation (AF) based on the CPA of risk factors (RF). Material and methods . A multicenter research was in period 2017–2026. The research subjects — patients with AF (n = 421), average age of 63 ± 4.2 years. The main research group (n = 303) included patients with paroxysmal AF during periods between paroxysms. The control group (n = 118) included patients with persistent AF after restoration of sinus heart rhythm using: electrical impulse therapy — control group №1 (n = 67) and thermal ablation of the pulmonary vein orifices — control group №2 (n = 51). The research objectives were the prevalence of CVC RF, the process components of a medical organizational model for CVC prevention in patients with AF, and the medical social effectiveness of the model. The follow-up period of patients was 12 months. Research methods included literature review, statistical analysis, clinical physiological analysis, systematization and comparative analysis. Results . RF of CVC in patients with AF (more than 80% of patients in the group), with no significant differences between groups, included arterial hypertension, cardiac arrhythmia such as sinus tachycardia and extrasystole, chronic heart failure (CHF), and dorso- and cervicopathy. Compared to the control group, the main research group had significantly fewer patients with low physical activity (9% vs. 74.6%, p = 0.001) and frequent alcohol consumption (27% vs. 47%, p = 0.01). The process components of the medical organizational model for CVC prevention include a comprehensive patient-centered approach based on clinical management technology and artificial intelligence, clinical physiological analytics of the CVC RF. The proportion of patients with recurrent AF was 2% in the main group, 5% in control group №1, and 11% in control group №2. The increase in the proportion of adherent primary care patients over 12 months averaged 389%, with no significant difference between the groups. Stroke, myocardial infarction, death, or gastrointestinal bleeding were not identified in the all groups. The proportions of patients with CHF progression in the main and control groups after 12 months of follow-up were 3% and 13.56%, respectively (p = 0.025). Conclusion . Adherence of patients to primary care and cardiovascular prevention model based on the CFA FR contributed to a low rate of AF recurrence after successful restoration of sinus heart rhythm and progression of CHF, as well as the effective prevention of adverse clinical cardiovascular outcomes.